Integrating Apparent Conductance in Resistivity Sounding to Constrain 2D Gravity Modeling for Subsurface Structure Associated with Uranium Mineralization across South Purulia Shear Zone, West Bengal, India - Arkoprovo Biswas; Animesh Mandal; Shashi Prakash Sharma; William Kumar Mohanty (International Journal of Geophysics)
South Purulia Shear Zone (SPSZ) is an important area for the prospect of uranium mineralization and no detailed geophysical investigations have been carried out in this region. To delineate the subsurface structure in the present area, vertical electrical soundings using Schlumberger array and gravity survey were carried out along a profile perpendicular to the SPSZ. Apparent conductance in the subsurface revealed a possible connection from SPSZ to Raghunathpur. The gravity model reveals the presence of a northerly dipping low density zone (most likely the shear zone) extending up to Raghunathpur under a thin cover of granitic schist of Chotanagpur Granite Gneissic Complex (CGGC). The gravity model also depicts the depth of the zone of density low within this shear zone at ~400 m near Raghunathpur village and this zone truncates with a steep slope. Integration of resistivity and gravity study revealed two possible contact zones within this low density zone in the subsurface at depth of 40 m and 200 m. Our study reveals a good correlation with previous studies in Raghunathpur area characterized by medium to high hydro-uranium anomaly. Thus the conducting zone coinciding with the low gravity anomaly is inferred to be a possible uranium mineralized zone.